TRENDS IN ROUTE PLANNING WITH THE TOOLS OF INTELLIGENT DISTRIBUTION LOGISTICS - Szabó, Adél Anett; Illés, Béla; Bányai Tóth, Ágota (Advanced Logistic Systems - Theory and Practice, 2021)
The basic purpose of the article is to provide a sufficiently detailed and comprehensive overview about route planning concepts, logics, trends and opportunities for the relevant companies in the sector. Lack of resources or the strategic point of view or some other certain reasons are often obstruct the small and medium-sized companies to have a deep-dive validation of these factors - causing significant competitive disadvantages in terms of strategy and planning. If we do not see through properly the to-do tasks, possibly areas for development, managed by the operation we can significantly make harder decision-making process at any level. However, in the knowledge of all these, strategy of development or a possible system introduction – including methodology and required toold - can easily be determined.